Dystonic Head Tremor and the Coexistence of Headache. (2nd November 2017) - Hulzenga, Marit A.; Beumer, Debbie; Koehler, Peter J.
Background: Head tremor may be observed in the presence of cervical dystonia and sometimes coexists with headache. We wished to investigate the presence of headache in dystonic head tremor. Methods: We studied the files of 19 patients from our outpatient clinic (1997–2017) with dystonic head tremor and assessed the co-occurrence of headache. We also performed a literature search of the topic. Results: Cervicogenic headache was present in nearly 37% of patients with dystonic head tremor. More than 85% of our patients presented with a "no-no" head tremor. Discussion: Headache is common in dystonic head tremor. Cervicogenic headache seems to be more frequent in patients with dystonic head tremor than in the general population. Future studies should compare the presence of cervicogenic headache in essential head tremor patients with that in patients suffering from dystonic head tremor.